2013
DOI: 10.1002/jmr.2304
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the membrane engineering concept: evidence for the specific orientation of electroinserted antibodies and selective binding of target analytes

Abstract: Membrane engineering is a generic methodology for increasing the selectivity of a cell biosensor against a target molecule, by electroinserting target-specific receptor-like molecules on the cell surface. Previous studies have elucidated the biochemical aspects of the interaction between various analytes (including viruses) and their homologous membrane-engineered cells. In the present study, purified anti-biotin antibodies from a rabbit antiserum along with in-house prepared biotinylated bovine serum albumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The fact that the lower anti-PSA antibody concentration (0.25 ng/mL) produced the best results can be explained as follows: in accordance with previous reports [ 18 ], increasing the density of electroinserted antibodies on membrane-engineered cells and/or the concentration of target analytes above an upper limit is not associated with a titrimetric between the analyte (PSA) and the membrane- engineered carrier cells with the anti-PSA antibodies. This is due to the fact that the analyte-electroiserted antibody reaction involves an electromechanical stress at the site of antibody area on the membrane, triggering to membrane status changes such as conductivity and porosity [ 32 ]. Quite frequently, there is a limitation to the modification of cell membrane potential status caused by the increasing density of electroinserted antibodies, with lower densities producing better resolution of response.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the lower anti-PSA antibody concentration (0.25 ng/mL) produced the best results can be explained as follows: in accordance with previous reports [ 18 ], increasing the density of electroinserted antibodies on membrane-engineered cells and/or the concentration of target analytes above an upper limit is not associated with a titrimetric between the analyte (PSA) and the membrane- engineered carrier cells with the anti-PSA antibodies. This is due to the fact that the analyte-electroiserted antibody reaction involves an electromechanical stress at the site of antibody area on the membrane, triggering to membrane status changes such as conductivity and porosity [ 32 ]. Quite frequently, there is a limitation to the modification of cell membrane potential status caused by the increasing density of electroinserted antibodies, with lower densities producing better resolution of response.…”
Section: Resultsmentioning
confidence: 99%
“…Receptor molecules can vary from antibodies to enzymes to polysaccharides [50][51][52][53][54]. It has been previously proven [55] that this principle is associated, in a unique way, with certain changes in the cellular electric properties (in particular, cell membrane hyperpolarization) as a consequence of the interaction of the analytes under determination with the electroinserted molecules and therefore changes in the cellular structure.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, known as Molecular Identification through Membrane Engineering, is a generic cell-based assay principle for the determination of analytes, including biomolecules, on the basis of the specific and selective interaction of the target analytes with cellular biorecognition elements, the surfaces of which have been modified by the electroinsertion of target-specific antibodies. It has been previously demonstrated that the binding of the target molecules to the electroinserted antibodies resulted in a unique and measurable change in the electric properties of the biorecognition elements, in particular the hyperpolarization of the engineered cell membrane [14][15][16]. These changes can be measured by any appropriate bioelectric/bioelectrochemical sensor.…”
Section: Introductionmentioning
confidence: 99%